2011
DOI: 10.4061/2011/654304
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation of Diastolic Dysfunction with Tissue Doppler Echocardiography in Women with Subclinical Hypothyroidism and the Effect of L-Thyroxine Treatment on Diastolic Dysfunction: A Pilot Study

Abstract: Background. Subclinical hypothyroidism (SH) predominantly affects women. The necessity of treatment in SH is controversial. Objective. We aimed to investigate the response of diastolic dysfunction to thyroid hormone replacement therapy (THRT) in women. Methods and Results. Twenty-two female subjects with SH and 20 euthyroid female controls were enrolled. Baseline and follow-up biochemical, hormonal, and echocardiographic evaluations were performed. Repeat echocardiograms were performed three months after the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
19
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 25 publications
8
19
0
Order By: Relevance
“…A study by Erkan and cols. (33) showed results similar to ours. Therefore, a longer euthyroid state or more aggressive treatment for lowering TSH may be required to achieve a statistically significant increase in the E/A ratio, after treatment.…”
Section: Discussionsupporting
confidence: 90%
“…A study by Erkan and cols. (33) showed results similar to ours. Therefore, a longer euthyroid state or more aggressive treatment for lowering TSH may be required to achieve a statistically significant increase in the E/A ratio, after treatment.…”
Section: Discussionsupporting
confidence: 90%
“…Previously, Erkan et al 16 found that in adults with SH L-T4 replacement did not cause any significant change in LVESD and LVEDD. In a study involving 196 children and 72 adults, Nidorf et al 38 reported that height was the best predictor of LV end-diastolic dimension and LV length.…”
Section: Discussionmentioning
confidence: 89%
“…It is well known that cardiac function is impaired in adults and children with overt hypothyroidism and it can be reversed by L-T4 treatment 24–27. Several adult studies have recently shown that patients with SH had impaired myocardial contractility11 12 28–32 and diastolic dysfunction,13 28 33 which may also be reversed by L-T4 treatment 5 6 11–13 15 16. In the literature, only two studies evaluating cardiac functions of children with SH, which also have Down syndrome and obesity, are present 34 35.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, free T4 levels were inversely correlated with CRP, and higher free T4 levels showed an insignificant trend towards depressed LVEF; a finding different from the results of others studies of L-thyroxine supplement in subclinical hypothyroidism. 21,22 It is surprising that we found that a much higher mortality was caused by septic shock (66.7%) than cardiovascular events (20%). In another large retrospective study, immediate cause of death from cardiovascular events accounted for 41.2% and peritonitis was directly implicated in 15.2% of the overall deaths.…”
Section: Discussionmentioning
confidence: 84%